2008
DOI: 10.1007/s00429-008-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

The comparative distributions of the monoamine transporters in the rodent, monkey, and human amygdala

Abstract: The monoamines in the amygdala modulate multiple aspects of emotional processing in the mammalian brain, and organic or pharmacological dysregulation of these systems can result in affective pathologies. Knowledge of the normal distribution of these neurotransmitters, therefore, is central to our understanding of both the normal processes regulated by the amygdala and the pathological conditions associated with monoaminergic dysregulation. The monoaminergic transporters have proven to be accurate and reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 211 publications
(222 reference statements)
0
18
0
Order By: Relevance
“…The distribution of NET immunoreactivity (NET-ir) closely matched that of tritiated nisoxetine autoradiographic labeling of NET in the amygdala (Hipolide et al, 2005; Smith and Porrino, 2008). Light microscopy demonstrated that NET+ axons in the BLa almost always exhibited co-localization of DBH.…”
Section: Discussionmentioning
confidence: 62%
“…The distribution of NET immunoreactivity (NET-ir) closely matched that of tritiated nisoxetine autoradiographic labeling of NET in the amygdala (Hipolide et al, 2005; Smith and Porrino, 2008). Light microscopy demonstrated that NET+ axons in the BLa almost always exhibited co-localization of DBH.…”
Section: Discussionmentioning
confidence: 62%
“…Globus pallidus (Mrzljak et al, 1996) DRD5 (4p16) Whole brain high expression and receptor density Whole brain moderate expression Cerebellum, substantia nigra, hypothalamus, striatum, cerebral cortex, nucleus accumbens, hippocampus and olfactory tubercle (Beischlag et al, 1995;Khan et al, 2000) DBH (9q34) Medulla, pons Whole brain moderate expression Noradrenergic brain stem nuclei, sympathetic ganglion neurons (Hoyle et al, 1994) and hypothalamus, substantia nigra (Westlund et al, 1988) Catecholamines: norepinephrine SLC6A2/NET1 (16q12) Very low expression and receptor density in the brain Whole brain moderate expression Locus coeruleus (Eymin et al, 1995). Amygdala (Smith and Porrino, 2008) ADRA2A (10q25) Very low expression and receptor density in the brain Moderate expression whole brain. Cerebellum (Schambra et al, 2005) Other monoamines MAOA ( (Zill et al, 2007).…”
Section: Gene Expressionmentioning
confidence: 98%
“…A study in the squirrel monkey (which occupies a different suborder than the Macaque) shows high TH-positive fiber densities in a region that may encompass the lateral PL, although the PL was not delineated in this study. Immunohistochemical localization of the dopamine transporter (DAT) indicates that there are many DAT+ fibers in the macaque ‘amygdalopiriform’ zone (CTA), which merges with the PL (although the PL was not specifically examined) (Ciliax et al, 1999; Smith and Porrino, 2008). In our material, there are no DAT-positive fibers in the Macaque PL or CTA (personal observations, not shown).…”
Section: Immunohistochemical Profile Of the Plmentioning
confidence: 99%